A population of faint low surface brightness galaxies in the Perseus cluster core - Wittmann, Carolin; Lisker, Thorsten; Ambachew Tilahun, Liyualem; Grebel, Eva K. (Monthly notices of the Royal Astronomical Society, 2017)
We present the detection of 89 low surface brightness (LSB), and thus low stellar density galaxy candidates in the Perseus cluster core, of the kind named ‘ultra-diffuse galaxies’, with mean effective V-band surface brightnesses 24.8-27.1 mag arcsec−2, total V-band magnitudes −11.8 to −15.5 mag, and half-light radii 0.7-4.1 kpc. The candidates have been identified in a deep mosaic covering 0.3 deg2, based on wide-field imaging data obtained with the William Herschel Telescope. We find that the LSB galaxy population is depleted in the cluster centre and only very few LSB candidates have half-light radii larger than 3 kpc. This appears consistent with an estimate of their tidal radius, which does not reach beyond the stellar extent even if we assume a high dark matter content (M/L = 100). In fact, three of our candidates seem to be associated with tidal streams, which points to their current disruption. Given that published data on faint LSB candidates in the Coma cluster - with its comparable central density to Perseus - show the same dearth of large objects in the core region, we conclude that these cannot survive the strong tides in the centres of massive clusters.
Gesehen am 13.09.2017